Facebook usage among university students and its association with their psychological and social well being - Wijewickrama, P.S.A.; Zafras, M.Z.M.; Wimalarathna, L.A.M.K.; Chinniah, T.R. (My University, 2012)
Facebook is a social networking site introduced in 2004, having more than 400 million users up to date. In Sri Lanka, most users are in the age group 18- 24 years. Many studies done in Western countries have found that Facebook has more positive consequences on an individual rather than a negative impact.